ATTITUDE AND BEHAVIOR OF RELIGIOUS FIGURE AHLUSSUNNAH WAL JAMAAH IN FACING THE COVID-19 PANDEMIC - Faraz, Faraz; Ashadi, Willi; Nashori, Fuad; Rabbani, Muhammad Dhia Rafid; Bengke, Kamelia Derbi; Musa, Muwaga (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2022)
This research aims to find out the thoughts, attitudes, and actions of Islamic religious authorities (ulama, kyai, or ustad) concerning the COVID-19 epidemic. This investigation was prompted by the fact of the enormous number of kyai or ulama who were exposed to COVID-19. The research technique ised mixed methods, essentially mixing qualitative and quantitative methodologies. The participants involved in the first (qualitative) stage were 14 persons, 13 males and 1 woman. They are Islamic religious figures who live in the Special Region of Yogyakarta. The second step was conducted by utilizing a questionnaire (Google form) and succeeded to gather 85 participants. The findings indicated that although all the participants were Ahlussunah Wal Jamaah (NU and Muhammadiyah), the discrepancies in their ideas, attitudes, and conduct regarding the COVID-19 epidemic were obvious. On average, Muhammadiyah is more inclined or tends to think towards complete endeavour, or its method of thinking tends to be Jabariyah, whereas NU is more likely to think towards entire submission or Qodariah, however certain situations are the contrary. This data demonstrates that in the face of a novel phenomena involving an unknown virus such as COVID-19, Indonesian Muslims, particularly Islamic religious leaders, cling to what they believe, not changing the norm.